Workforce diversity and employee performance: Examining the moderating role of organizational culture in Malaysian private universities - Norzanah Mat Nor; Hamidey Hamid; Shaliza Alwi (Environment and Social Psychology, 2025)
This study investigates the effect of various dimensions of workforce diversity, including age, gender, ethnicity, and educational background, on employee performance, while also considering organisational culture as a moderating factor. A quantitative research design was utilised to gather data from academic and administrative personnel at various private higher education institutions (PHEIs) in Malaysia. The study employed Partial Least Squares Structural Equation Modelling (PLS-SEM) to investigate the relationships among variables, offering empirical insights into the impact of diversity in higher education contexts. The findings demonstrate that each of the four diversity dimensions has a positive impact on employee performance, suggesting that workplaces characterised by inclusivity and diversity promote innovation, collaboration, and overall institutional effectiveness. Among the various factors influencing diversity, gender diversity exhibited the most significant impact on performance outcomes, highlighting the critical need for balanced representation in academic settings. While organisational culture showed a positively correlated with performance, it did not significantly influence the relationship between diversity and performance. This indicates that culture plays a more direct role in enhancing organisational well-being instead of acting as a moderating factor. The results enhance comprehension of diversity management in the Malaysian higher education landscape by merging Social Identity Theory with quantitative modelling techniques. The study emphasises how leaders in higher education can utilise diversity to improve productivity, equity, and the competitiveness of their institutions. This study adds to worldwide conversations regarding inclusive human resource strategies that are in harmony with social sustainability and the objectives of excellence in higher education.